CFD simulation of the unsteady flow of a single coal log in a pipe. (17th September 2015) - Li, Wenjuan; Lu, Shengyong; Liu, Yong; Wang, Rupei; Huang, Qunxing; Yan, Jianhua
Abstract This study proposes a numerical simulation of the unsteady turbulent flow of a single coal log in a pipe using a dynamic mesh method. An eccentric two‐dimensional dynamic model is developed in FLUENT 6.2. The model contains a straight section and a bent section. Comparisons of the coal log velocity and the pressure distributions of the pipe and the coal log surface are made between the calculated results and the experimental data. The shear force and the friction coefficient are also calculated to verify changes of the influence of water on the coal log. The results of this simulation display the dynamic motion of the coal log for startup and turning. Water drag force moves the coal log, making the coal log velocity greater than the water velocity. The lifting force lifts the coal log and moves its tail slightly upward. The pressure drop of the whole pipe is respectively larger in the presence of the coal log. The pressure along the coal log surface slowly declines. The appearance of a bend impedes the motion of the coal log and enhances abrasion. The coal log has difficulty being suspended due to decreased lifting force and increased friction. The pressure on the coal log surface rises.